In‐house chemical library repurposing: A case example for Pseudomonas aeruginosa antibiofilm activity and quorum sensing inhibition. Issue 8 (6th October 2018) - Ravithej Singh, L; Tripathi, Vikash C.; Raj, Sneha; Kumar, Anoop; Gupta, Sampa; Horam, Soyar; Upadhyay, Akanksha; Kushwaha, Pragati; Arockiaraj, Jesu; Sashidhara, Koneni V.; Pasupuleti, Mukesh
Abstract: Hit, Lead & Candidate Discovery Drug repurposing has become a recent trend in drug development programs, where previously developed drugs are explored for hit and redeveloped into potential therapeutic agents for new diseases. Globally, in any drug development program, a series of molecules are synthesized and evaluated for the hypothesized activity. Hits are developed into lead molecules or drugs, whereas the negative ones are shelved in the lab with no immediate use. We in this project took the previously sidelined small chemical molecules to the next level of utility, where previously developed in‐house small molecules library are tested for the unexplored biological relevant activity. As biofilm formation and quorum sensing play a vital role in bacterial pathogenesis, we believe that they could be one of the most effective targets for antimicrobial agents. In this study, we report the evaluation of 50 different compounds for anti‐biofilm and anti‐quorum sensing activity against Pseudomonas aeruginosa . Out of the screened compounds, three hydrazine‐carboxamide hybrid derivatives showed promising anti‐biofilm property and inhibition of pyocyanin production without any direct antimicrobial activity and cytotoxicity issues. Hydrazine‐carboxamide hybrids can be a new class and promising leads for further anti‐biofilm and anti‐virulence development against microbial infections.